(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Humans have used medicinal plants for thousands of years as natural remedies to prevent, treat and manage various health conditions. The fragrant Boswellia dalzielii plant, is primarily found on rocky, arid, and shallow soils in the West African Savannah region. Antibacterial activity of aqueous and ethanolic extracts of Boswellia dalzielii stem bark were tested against clinical isolates of E.coli and S.Typhi. Phytochemical tests were conducted to identify the classes of compounds present, the idendity, characteristic structures the various compounds were identified using Gas chromatography-Mass Spectrometric analysis (GC-MS) at the department of Chemistry, ABU, Zaria. Antibacterial activity of the extracts were assessed using agar well diffusion method. Flavonoids, saponins, alkaloids and phenols were detected in both ethanolic and aqueous extracts, while GC-MS analysis revealed presence of n-hexadecanoic acid, 9-octadecanoic acid and a trace amount of some lipophilic acids. Antibacterial activity of the extract against the bacterial isolates (Salmonella spp. and E. Coli) revealed varied degrees of antibacterial activity. In contrast to aqueous extracts, the ethanolic extract had a comparatively higher zone of inhibition. , the zone of inhibition ranged from 8.00 mm to 16.0 mm, which was much greater than when utilizing an aqueous extract (6.00 mm to 14.0 mm). Both the minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations were also recorded. The findings of this study suggested that Boswellia dalzielii stem bark would serve as an important source of medicinal compound which could be harnessed for antibacterial activity.